CNS: Not an immunoprivilaged site anymore but a virtual secondary lymphoid organ. (2nd January 2018) - Negi, Neema; Das, Bimal K.
ABSTRACT: The cardinal dogma of central nervous system (CNS) immunology believed brain is an immune privileged site, but scientific evidences gathered so far have overturned this notion proving that CNS is no longer an immune privileged site, but rather an actively regulated site of immune surveillance. Landmark discovery of lymphatic system surrounding the duramater of the brain, made possible by high resolution live imaging technology has given new dimension to neuro-immunology. Here, we discuss the immune privilege status of CNS in light of the previous and current findings, taking into account the differences between a healthy state and changes that occur during an inflammatory response. Cerebrospinal fluid (CSF) along with interstitial fluid (ISF) drain activated T cells, natural killer cells, macrophages and dendritic cells from brain to regional lymph nodes present in the head and neck region. To keep an eye on inflammation, this system hosts an army of regulatory T cells (CD25+ FoxP3+) that regulate T cell hyper activation, proliferation and cytokine production. This review is an attempt to fill the gaps in our understanding of neuroimmune interactions, role of innate and adaptive immune system in maintaining homeostasis, interplay of different immune cells, immune tolerance, knowledge of communication pathways between the CNS and the peripheral immune system and lastly how interruption of immune surveillance leads to neurodegenerative diseases. We envisage that discoveries should be made not only to decipher underlying cellular and molecular mechanisms of immune trafficking, but should aid in identifying targeted cell populations for therapeutic intervention in neurodegenerative and autoimmune disorders.